Exploring the relationship between job crafting and resilience - Nameera Munnisunker; Nelesh Dhanpat (SA Journal of Human Resource Management)
Orientation: Employees undertake self-initiated processes like job crafting to reshape their work. Within financial services organisations where work is characterised by high pressure and demanding conditions, assessing relationships between job crafting and resilience becomes particularly interesting.